Analysis, assessment, and damage mitigation of road tunnel subjected to BLEVE - Cheng, Ruishan (Curtin University, 2023)
This thesis presents the analysis, assessment, and damage mitigation of road tunnels subjected to Boiling Liquid Expansion Vapor Explosions (BLEVEs). The study systematically investigates the performance and response of various types of road tunnels under BLEVEs, aiming to develop accurate prediction models for structural response, reliable methods for damage assessment, and effective measures for damage mitigation. The findings of this research can offer valuable insights for the design of road tunnels against BLEVEs.